2021
DOI: 10.1002/pds.5396
|View full text |Cite
|
Sign up to set email alerts
|

Use of negative control outcomes to assess the comparability of patients initiating lipid‐lowering therapies

Abstract: Purpose Clinical trials have demonstrated efficacy of proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) in reducing risk of cardiovascular disease events, but effectiveness in routine clinical care has not been well‐studied. We used negative control outcomes to assess potential confounding in an observational study of PCSK9i versus ezetimibe or high‐intensity statin. Methods Using commercial claims, we identified U.S. adults initiating PCSK9i, ezetimibe, or high‐intensity statin in 2015–2018, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The risk of decubitus ulcer among PCSK9i initiators was consistently lower (risk ratios 0.4-0.7), while risks of vaccinations tended to be higher (risk ratios 1.1-1.2 for some contrasts). 21 A subsequent NCO study can determine whether bias may be sufficiently reduced through more stringent inclusion criteria to balance patients' health status and healthcare access. Another design-driven approach would be to refine the comparator definition.…”
Section: Calibrate Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The risk of decubitus ulcer among PCSK9i initiators was consistently lower (risk ratios 0.4-0.7), while risks of vaccinations tended to be higher (risk ratios 1.1-1.2 for some contrasts). 21 A subsequent NCO study can determine whether bias may be sufficiently reduced through more stringent inclusion criteria to balance patients' health status and healthcare access. Another design-driven approach would be to refine the comparator definition.…”
Section: Calibrate Resultsmentioning
confidence: 99%
“…For example, in the NCO study of patients initiating lipid‐lowering therapies, results suggested patients with less frailty and higher healthcare utilization were more likely to be prescribed a PCSK9i compared with patients initiating statins or ezetimibe. The risk of decubitus ulcer among PCSK9i initiators was consistently lower (risk ratios 0.4–0.7), while risks of vaccinations tended to be higher (risk ratios 1.1–1.2 for some contrasts) 21 . A subsequent NCO study can determine whether bias may be sufficiently reduced through more stringent inclusion criteria to balance patients' health status and healthcare access.…”
Section: Practical Considerations For Nco Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, interactive data visualization tools can allow the user to easily browse a large volume of results from the many combinations of analyses that are performed. For example, in a negative control outcome study of lipid‐lowering therapies, 43 results from multiple outcomes, cohorts, and subgroups are easily explored using simple interactive graphs and tables 44 . Similarly, the Observational Health Data Science Initiative has created R packages to allow results from pharmacoepidemiologic studies to be explored via R/Shiny applications 45 .…”
Section: Future Of Visualizationmentioning
confidence: 99%